Nonlinear optical and spectroscopic properties, thermal analysis, and hemolytic capacity evaluation of quinoline-1,3-benzodioxole chalcone (2024)
This article describes the synthesis, characterization (1H NMR, 13C NMR, FT-IR, HRMS and XRD), UV-Vis absorption and fluorescence spectra, theoretical analysis, evaluation of nonlinear optical properties (NLO), thermal analysis and determination of the hemolytic capacity of the compound (E)-N-(4-(3(benzo[d][1,3]dioxol-5-yl)acryloyl)phenyl)quinoline-3-carboxamide (5). Radiological findings showed that compound 5 crystallized in space group Pca21. Furthermore, theoretical DFT studies performed with the B3LYP and M062X functionals showed good agreement with the experimental results and provided valuable information on the molecular and electronic structure, reactivity, polarizability, and kinematic stability of the compound. Besides, compound 5 did not show any hemolytic effect on human erythrocytes and exhibited strong NLO properties. The TG and DTA thermograms of quinoline–chalcone (5) revealed a multi-step thermal decomposition process with a total mass loss of 83.2%, including water content loss. The DTA curves exhibited endothermic peaks corresponding to decomposition steps, melting point, and thermochemical transition. Additionally, exothermic peaks in the DTA thermograms align with significant mass loss, confirming the compound's melting point and water content, as validated by X-ray diffraction analysis. These results contribute to the advancement of research on compounds with NLO properties and offer a promising avenue for the development of substances potentially applicable to optical devices in the biomedical field.